1970
DOI: 10.4314/evj.v20i2.9
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro antibacterial activity of rumex nervosus, plantago lanceolata, solanum incanum and lepidium sativum against selected bacterial pathogens of human and animals

Abstract: Medicinal plants are used as a primary means of tackling different ailments especially in developing countries. In the present study, the leaves of Rumex nervosus, Plantago lanceolata, Lepidium sativum and Solanum incanum were collected and extracted by maceration method using 70% methanol. The extracts were concentrated and the yields recorded. Antibacterial effects of the extracts were tested on selected bacteria such as Streptococcus, S. aureus, L. monocytogenes, E. coli, and Salmonella which were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…This finding was different with other studies revealed that the least activity was recorded against E. coli. 7,16 In addition, our results was different with a study conducted by Kasimala et al, 17 on methanol extract of Rumex nervosus had also showed no antibacterial activity against E.coli and S. aureus. Where as, our results reported that highly antibacterial activity against E.coli and S. aureus.…”
Section: Discussioncontrasting
confidence: 96%
“…This finding was different with other studies revealed that the least activity was recorded against E. coli. 7,16 In addition, our results was different with a study conducted by Kasimala et al, 17 on methanol extract of Rumex nervosus had also showed no antibacterial activity against E.coli and S. aureus. Where as, our results reported that highly antibacterial activity against E.coli and S. aureus.…”
Section: Discussioncontrasting
confidence: 96%
“…Although the results of this study support the findings of Al-Nowihi et al [21] on the high activity of R. nervosus against S. aureus, our results contradict their findings with respect to E. coli, where they demonstrated that R. nervosus had a strong growth inhibitory effect on E. coli among Gram-negative bacteria in both ethanolic and methanolic solvents. However, the obtained result regarding the effect of R. nervosus extracts on E. coli is in agreement with other studies, which showed that the extract of R. nervosus had the lowest anti-E. coli activity [49,50].…”
Section: Discussionsupporting
confidence: 92%
“… 49 Also, a previous study done in Ethiopia showed that this plant demonstrated antibacterial activities against Listeria monocytogenes, Streptococcus, S. aureus, Salmonella , and E. coli . 50 In addition, P. lanceolata leaf extract in various solvents also exhibited antibacterial activity against S. pneumoniae , MRSA, S. aureus, S. boydii, E. coli , and K. pneumoniae . 51…”
Section: Discussionmentioning
confidence: 98%
“…49 Also, a previous study done in Ethiopia showed that this plant demonstrated antibacterial activities against Listeria monocytogenes, Streptococcus, S. aureus, Salmonella, and E. coli. 50 In addition, P. lanceolata leaf extract in various solvents also exhibited antibacterial activity against S. pneumoniae, MRSA, S. aureus, S. boydii, E. coli, and K. pneumoniae. 51 Matricaria recutita was another active plant incorporated in our study; EtOAc and EtOH extracts of this plant revealed promising antimicrobial activity against the test ATCC bacteria, while it showed only a lower activity level against MDR isolates.…”
Section: Dovepressmentioning
confidence: 98%